The Adolescents Psychosocial Phenomenology of Online Gaming Addiction in Surau Gadang Sub District Nanggalo of Padang - Nike Puspita Alwi; Mustikasari . (Elevate, 2018)
Background: Online gaming addiction nowadays is a global problem. The most vulnerable age group to online game addiction are the adolescents. Many studies has shown that online gaming addiction gave negative impacted on adolescent psychosocial gamers. Purpose: To explore the psychosocial phenomenology of onine gaming addiction of adolescents. Method: The design of this study was a qualitative method with phenomenology approach. There are 6 participants gamer was selected by purposive sampling technique and followed by one parent as the triangulation method. Findings: There were seven themes that retrieved from this study: reason for playing; thought while playing; feeling towards online games; characteristic of online gaming addiction; psychosocial impassing; effort to escape from addict playing; gamers wishes about their addict playing. Conclusion: Reason for playing, thought while playing and feeling towards online games give contribution to online gaming addiction in adolescents and the psychosocial impassing has main issue that could be seen by parent too. It’s recommended to Indonesian psychiatric nurse to do sreenning of this addiction then collaborate with school in order to control online gaming addicton through SBMHS (School Based Mental Health Services) and give CBT to treatment the addict gamer.